2021
DOI: 10.1002/tcr.202100150
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals of Hysteresis in Perovskite Solar Cells: From Structure‐Property Relationship to Neoteric Breakthroughs

Abstract: Perovskite solar cells (PSC) have shown a rapid increase in efficiency than other photovoltaic technology. Despite its success in terms of efficiency, this technology is inundated with numerous challenges hindering the progress towards commercial viability. The crucial one is the anomalous hysteresis observed in the photocurrent density‐voltage (J−V) response in PSC. The hysteresis phenomenon in the solar cell presents a challenge for determining the accurate power conversion efficiency of the device. A detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 137 publications
0
21
0
Order By: Relevance
“…78.8% and 20.1% (Supplementary Table 2). This can be explained with the constructed molecular bridge for efficient carrier transportation as well as the defect passivation [33][34][35] . The external quantum efficiency spectra along with the integrated J SC , ca.…”
Section: Photovoltaic Performancesmentioning
confidence: 99%
“…78.8% and 20.1% (Supplementary Table 2). This can be explained with the constructed molecular bridge for efficient carrier transportation as well as the defect passivation [33][34][35] . The external quantum efficiency spectra along with the integrated J SC , ca.…”
Section: Photovoltaic Performancesmentioning
confidence: 99%
“…The degradation of the perovskite is caused by external factors such as moisture, oxygen, temperature, and UV radiation, and internal factors such as crystal structure, ion migration, and interfacial contacts. 10,45 Furthermore, the fabrication process, constituent materials, and device architecture also affect the stability of PSCs. 46 Besides these factors, it has been observed that the inverted (p-i-n) PSCs are more stable than the regular (n-i-p) PSCs.…”
Section: Strategies For Improving the Stability Of Inverted Pscs With...mentioning
confidence: 99%
“…During the measurement of the current J-V response of PSCs, a hysteresis between the forward and reverse scan has been reported. [73,74] Typically, two types of J-V hysteresis behaviors are reported in literature namely: (i) normal-hysteresis (NH) and (ii) inverted-hysteresis (IH). In a NH, PSC exhibits higher performance in forward to reverse (F-R) direction compared with reverse to forward (R-F) scan (Figure 8a), whereas, in an IH, the performance during R-F scan is higher than F-R scan (Figure 8b).…”
Section: Relation Between Capacitance Spectra and J-v Hysteresismentioning
confidence: 99%
“…During the measurement of the current J‐V response of PSCs, a hysteresis between the forward and reverse scan has been reported [73,74] . Typically, two types of J‐V hysteresis behaviors are reported in literature namely: (i) normal‐hysteresis (NH) and (ii) inverted‐hysteresis (IH).…”
Section: Relation Between Capacitance Spectra and J‐v Hysteresismentioning
confidence: 99%